Comparative Analysis of Gender Differences in Academic Self-Efficacy, Motivation, School Climate, and Well-Being Among High School Student - Hernawati, Neti; Rifameutia, Tjut; Royanto, Lucia R.M. (Psympathic : Jurnal Ilmiah Psikologi, 2025)
Gender differences in academic self-efficacy, motivation, and school climate provide critical insights into variations in student learning experiences and outcomes. Therefore, this study aims to examine how these factors influence well-being among Indonesian high school student and explore the effect of gender on these relationships. Using a cross-sectional design, data were collected from 401 student aged 14–18 years across 36 public school in 16 provinces through an online questionnaire. The results showed that academic self-efficacy and school climate significantly and positively predicted well-being for both male and female student. Academic motivation showed no significant effect among males but had a positive influence among females. These results underscore the importance of strengthening student self-efficacy and creating supportive school environments. Furthermore, this study emphasizes the need for gender-sensitive approaches in educational programs that address motivational dynamics to effectively promote student well-being.